2021
DOI: 10.1108/jaee-02-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting practices and efficiency in a Colombian multi-utility conglomerate

Abstract: PurposeThe purpose of this paper is to examine how a state-owned Colombian multi-utility conglomerate (CMC) has used management accounting practices (MAPs) to shape efficiency. The authors bring out the interplay between structures and agency in the process of shaping efficiency, which has enabled the company to operate as a private enterprise, taking advantage of NPM-led reforms and management accounting technologies.Design/methodology/approachThis is an interpretative case study of a CMC. Data for the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…A number of critical studies conducted in emerging economy contexts have therefore alleged that NPM has eroded values typically associated with the public sector by imposing businesslike practices and further damaging the process of democratic control (Hopper, 2017;Nyamori et al, 2017). Many of these studies have also demonstrated how the growing influence of neoliberalism supported by NPM has resulted in the state becoming a protector of big businesses and a market promoter, further commodifying and, in some cases, worsening, public service delivery (Barrios-Álvarez et al, 2021;Varela, 2008a;Wickramasinghe et al, 2021). Hopper (2017) argued that achieving development goals through these internationally prescribed reforms therefore appears to be unrealistic.…”
Section: Development Npm and Emerging Economies: Contemporary Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of critical studies conducted in emerging economy contexts have therefore alleged that NPM has eroded values typically associated with the public sector by imposing businesslike practices and further damaging the process of democratic control (Hopper, 2017;Nyamori et al, 2017). Many of these studies have also demonstrated how the growing influence of neoliberalism supported by NPM has resulted in the state becoming a protector of big businesses and a market promoter, further commodifying and, in some cases, worsening, public service delivery (Barrios-Álvarez et al, 2021;Varela, 2008a;Wickramasinghe et al, 2021). Hopper (2017) argued that achieving development goals through these internationally prescribed reforms therefore appears to be unrealistic.…”
Section: Development Npm and Emerging Economies: Contemporary Discussionmentioning
confidence: 99%
“…The interconnection between management accounting and the notion of efficiency has been discussed in prior research conducted using interpretative approaches (Ahrens & Chapman, 2004;Barrios-Álvarez et al, 2021). Available evidence illustrates how MAPs have been devised to redefine what is efficient and profitable for organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En 2017 se publicaron dos trabajos de contabilidad social y ambiental (Macías & Farfán-Liévano, 2017;Sinforoso et al, 2017) y a partir de ellos fueron surgiendo otros artículos en importantes revistas internacionales. El mayor grupo es sobre contabilidad no financiera (Cabrera-Narváez & Quinche-Martín, 2021;Correa-García et al, 2020;Quinche-Martín & Cabrera-Narváez, 2020), pero también hay otros trabajos muy destacados sobre historia de la contabilidad (Quintero, 2020;Rico-Bonilla, 2020), la relación contabilidad y género (Chamorro et al, 2020;Rico-Bonilla, 2020), covid-19 (Alba-Cabañas & Gómez, 2021Gómez & Alba-Cabañas, 2020;Sangster et al, 2020), sobre contabilidad gubernamental (León-Silva et al, 2020;Ocampo-Salazar, 2020) y sobre contabilidad de gestión (Barrios Álvarez et al, 2021).…”
Section: Integración Con Las Discusiones Extrarregionalesunclassified
“…This method was used, for example, by Frishammar et al [60] to present an omnichannel strategy typology showing how shopping malls can meet the evolving digitalization challenge; by Alvarez et al [61] to examine how a state-owned Colombian multiutility conglomerate has used management accounting practices to shape efficiency; and by Diab [62] to provide a political explanation of management, accounting, and control practices in a traditional and unstable African setting.…”
Section: Interpretative Case Studymentioning
confidence: 99%